Mekarsari village towards sustainable tourism village: A literature review - Putra, Bayu Karunia; Azizah, Nanik; Izzati, Inayatul; Laili, Yayuk Nurhidayatul; Aini, Dinatul; Maulana, Arkan; Hamdani, Muhamad Sohibul; Hafifah, Patin; Nurjannah, Siti; Aprilia, Hilma; Islam, Muhamad Saiful; Saputra, Satriawan Arya; Zamroni; Noviana (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: A tourism village is a rural area designed or developed as a tourist destination by utilizing diverse local potentials. These potentials may include natural beauty, culture, traditions, handicrafts, cuisine, and local community activities that attract tourists. A tourism village serves as a place for recreation, education, and sustainable development of the local economy. Findings: [a] Empowering local communities: Active involvement of local communities is essential to maintaining the sustainability of tourism villages. Empowered communities can take a leading role in managing tourism activities, such as tour guides, homestay operators, or local artisans. Training programs and capacity-building initiatives are often vital to help communities adapt to tourists' needs while preserving their cultural identity. [b] Preservation of local culture: Sustainable tourism villages support the preservation of cultural heritage, such as traditions, arts, and local crafts. This creates a unique attraction for tourists while safeguarding local culture from extinction. Practices such as routine cultural performances, traditional festivals, and the promotion of local products are essential strategies. [c] Environmental conservation: Proper waste management, such as recycling systems or reducing plastic waste. Use of renewable energy, like solar panels or micro-hydro systems. Protection of local ecosystems, such as forests, rivers, or coral reefs. Methods: The method used is a literature review through a research approach conducted by collecting, analyzing, and evaluating relevant literature on a specific topic, based on scientific journals, books, conference proceedings, reports, and articles. Conclusion: [a] Empowering local communities: Sustainable tourism villages prioritize the involvement of local communities as the main actors in tourism management. This includes participation in planning, management, and benefiting from tourism activities. [b] Environmental conservation: In sustainable tourism villages, the use of natural resources is regulated to avoid damaging ecosystems. Waste management, the use of renewable energy, and the protection of biodiversity are essential components. [c] Economic sustainability: Tourism villages should create stable and equitable economic opportunities, including generating new jobs, supporting micro, small, and medium enterprises (MSMEs), and promoting village economic growth without overexploiting local resources. [d] Preservation of culture and traditions: Sustainable tourism villages protect and promote local culture and traditions, making them a key attraction while maintaining the identity of the local community. [e] Multi-stakeholder collaboration: Sustainable tourism villages require support from various stakeholders, including government, private sectors, academics, and the community, to ensure effective management and development.